Influencia del ejercicio físico en el metabolismo proteico de ratas con hipertiroidismo - Papini, Camila B.; Corazza, Danilla I.; Júnior, Marcelo C. [UNESP]; Dalia, Rodrigo [UNESP]; Luciano, Eliete [UNESP] (My University, 2014)
Background: One of functions of the thyroid hormones is to regulate body metabolism, including the increase of the protein synthesis. Thus, dysfunction in these hormones can lead to decreased physical exertion tolerance, because include the cardiovascular and musculoskeletal system. The objective of this study was to investigate the influence of physical exercise in the protein metabolism in rats induced to hyperthyroidism. Methods: The sample was composed of 45 young Wistar rats, divided into 4 groups: Sedentary Control, Trained Control, Hyperthyroidism Sedentary and Hyperthyroidism Trained. Experimental hyperthyroidism was induced with daily administration of levothyroxine (T4) during 10 days preceding the lactate minimum test. The training protocol consisted of swimming exercise (1 hour/day), 5 days per week for 4 weeks, with overload corresponding to 80% load obtained from the lactate minimum test. Were performed normality test with Shapiro-Wilk, analysis of variance (ANOVA), and critical level of significance fixed on 5% (p< 0,05). Results: The analysis of Ratio Protein/DNA showed that the induction of hyperthyroidism promoted liver hypertrophy, but the exercise protocol used in our study was able to prevent hepatotrophy. There were no changes in the metabolism of plasma and tissues proteins in cardiac and skeletal muscle tissues. Conclusion: In conclusion, the model used was able to induce the animals to hyperthyroidism. The results showed an increase in hepatic tissue proteins when the hyperthyroidism was associated with physical exercise. Is important to highlight the need for further studies to investigate the effects of different types of exercise, as well as the intensity and periods of training.
Influence of physical exercise on proteins metabolism in rats with hyperthyroidism
Keywords: Hyperthyroidism; Physical exercise; Proteins metabolism; Rats